The main problems of modernization agro-industrial complex of the Kyrgyz economy (Journal of Economic Research & Business Administration, 2015)
This article focuses on the innovative development of agriculture of the Republic of Kyrgyzstan . According to the author , it is necessary to pay special attention to the innovative development of agriculture of the Republic of Kyrgyzstan .
Keywords: innovative development; Agriculture